A conceptual framework and metrics for evaluating multicomponent interventions to increase colorectal cancer screening within an organized screening program. Issue 21 (25th October 2018) - Subramanian, Sujha; Hoover, Sonja; Tangka, Florence K. L.; DeGroff, Amy; Soloe, Cynthia S.; Arena, Laura C.; Schlueter, Dara F.; Joseph, Djenaba A.; Wong, Faye L.
Abstract : Background: Multicomponent, evidence‐based interventions are viewed increasingly as essential for increasing the use of colorectal cancer (CRC) screening to meet national targets. Multicomponent interventions involve complex care pathways and interactions across multiple levels, including the individual, health system, and community. Methods: The authors developed a framework and identified metrics and data elements to evaluate the implementation processes, effectiveness, and cost effectiveness of multicomponent interventions used in the Centers for Disease Control and Prevention's Colorectal Cancer Control Program. Results: Process measures to evaluate the implementation of interventions to increase community and patient demand for CRC screening, increase patient access, and increase provider delivery of services are presented. In addition, performance measures are identified to assess implementation processes along the continuum of care for screening, diagnosis, and treatment. Series of intermediate and long‐term outcome and cost measures also are presented to evaluate the impact of the interventions. Conclusions: Understanding the effectiveness of multicomponent, evidence‐based interventions and identifying successful approaches that can be replicated in other settings are essential to increase screening and reduce CRC burden. The use of common framework, data elements, and evaluation methods will allow the performance of comparative assessments of the interventions implemented across CRCCP sites to identify best practices for increasing colorectal screening, particularly among underserved populations, to reduce disparities in CRC incidence and mortality. Abstract : Multicomponent, evidence‐based interventions are increasingly viewed as essential to increase the use of colorectal cancer screening to meet national targets. The authors provide an overview of the framework, metrics, and data elements that were developed to evaluate the implementation processes, effectiveness, and cost effectiveness of multicomponent interventions used in the Centers for Disease Control and Prevention's Colorectal Cancer Control Program.